Reconfiguring the social and solidarity economy in a Danish/Nordic welfare context - Hulgård, Lars; Andersen, Linda Lundgaard (3rd EMES-Polanyi International Seminar. Welfare societies in transition. Polanyi revisited through the lens of welfare state, social democracy and solidarity economy, 2018)
When looking at definitions and understandings of the social and solidarity economy, one issue stands out as particularly significant. The issue of how it links to organizational (micro and meso level dimensions) and societal specificities. Whereas social enterprise also in the EMES ideal typical version (Borzaga & Defourny, 2001) is only indirectly linked to a Polanyian framework (Gardin, 2006), the notion of solidarity economy can hardly be understood at an elaborate level without reference to the Polanyian framework of plurality. Accordingly, in this paper we will first highlight the difference between adopting a social economy and a solidarity economy approach to social enterprise and social entrepreneurship. Within the framework of a social economy perspective, social enterprise is first defined through a set of organizational criteria leaving the relation to the broader and deeper issues of economy and democracy open. As a contrast to this, solidar-ity economy links the organizational dimension of a particular social enterprise to the broader political and economic framework of the particular society (Laville, 2010: 230 ff.). Secondly, we will present and discuss two specific social enterprises that both re-flects the diversity of social enterprise and social entrepreneurial initiatives in a Danish welfare context and provide important insights for developing theories on solidarity economy. The two initiatives differ in shape, space/geography and organizational struc-ture but are important examples of pluralism in a Danish welfare context (Andersen, 2015). Roskilde Festival and Skovgård Hotel share a number of features that place them as interesting agents of solidarity economy. They both display a differentiated activity portfolio of business; public and civil character and they display a differentiated profile of reciprocity, redistribution and democracy that place them as influential in local, regional and national/international contexts. Finally, in the concluding section we discuss how an analysis based upon solidari-ty economy differ from one based solely upon a social economy perspective, and second-ly some future perspectives for the continued evolution of the Danish/Scandinavian wel-fare model.
Keywords: Denmark; plurality; social economy; social enterprise; social entrepreneurship; solidarity economy

Reforming States, Agricultural Transformation, and Economic Development in Russia and Japan, 1853-1913 - Cohen, Mark (2015)
Capitalist economic development has occurred unevenly, as certain economies began sustained growth relatively early, opening up an increasingly large gap with lagging countries. This well-known fact has encouraged much research on the prospects for undeveloped economies to "catch up" to the earlier developers. Japan and Russia in the late nineteenth century were two of the first countries outside of western Europe to experience substantial catch-up growth. Beginning in the 1860s, political elites in both countries adopted wide-ranging reforms in pursuit of military modernization and its political and economic prerequisites. This paper analyzes the impact of the two states' reform programs on their countries' rural economies, which represented the vast majority of population and production. Adopting a Polanyian perspective on economic development, this paper finds that only in Japan were agrarian relations transformed so as to set off a process of capitalist economic development centered on rural areas. This divergence is explained by the different stances of the two reforming states towards landlords and peasant communities.
Keywords: Japan; Russia; economic development; rural economies

Denaturalizing the Market: Primitive Accumulation, Class Reformation, and the Rise of Colombia's Anti-Neoliberal Countermovement - Hough, Phillip A. (2015)
This paper addresses what labor movement scholars are calling the "Polanyi-problem" - how societal movements can effectively re-embed neoliberal markets back into society - by drawing upon recent interpretations of Karl Marx writings on primitive accumulation and class formation. The author focuses on the case of Colombia's coffee farmers (cafeteros) - a class of producers whose historically-privileged modality of class reproduction was undermined by the liberalization of the coffee market in the 1990s and who have engaged in two major waves of protest aimed at re-embedding the coffee market back into society (1993-2001; 2013-2014). While similar in terms of movement targets, tactics, and general goals, a significant shift has occurred in the cafeteros' demands which is reflective of a fundamental transformation of their class identity away from one that 'naturalized' their dependence upon the coffee market to meet their subsistence needs and towards one that 'de-naturalizes' their dependence upon this market. This 'denaturalizatization of the market' undermined their ability to mobilize around a privileged form of class identity. Yet, it provided them with the ability to generalize their struggle beyond the confines of the coffee economy and therefore develop into a broad, national anti-neoliberal agrarian Polanyian counter-movement.
Keywords: Colombia; Polanyi problem; countermovement; primitive accumulation; reembedding

Nationalist Politics and the Double Movement: The Problem of Legitimacy in Neoliberal States - Blad, Cory (2013)
This paper argues that the contemporary efficacy of nationalist politics is a strategic response to neoliberal conditions of state legitimation. Using the double movement as a theoretical framework, I argue that neoliberalism alters the policy alternatives available to state actors by reducing the viability of economic protectionist initiatives once dominant in the embedded liberal era. This policy capacity reduction inhibits some of the key means for state legitimation (e.g., public spending, regulatory protectionism), which exacerbate the negative effects of capitalist liberalization. As national populations view the state as unwilling or unable to mitigate economic adversities or provide traditional socio-economic services, significant potential exists for a delegitimation of state actors and institutions. In response, neoliberal state actors have gravitated toward an increasingly cultural rhetoric of nationalism as a means to maintain popular legitimacy. This shift goes beyond simple political power struggles - in accordance with the double movement framework, systemic global capitalism requires legitimate state authority to ensure both local stability and sustained capital accumulation. Neoliberal ideology, however, discourages traditional means of state legitimation. A Polanyian examination of this ironic condition offers a structural explanation for the increased efficacy of nationalist politics; however, it also raises serious questions about the sustainability of this legitimation strategy.
Keywords: double movement; globalization; nationalism; neoliberalism; state legitimation

Economic support personal networks of rural entrepreneurships - Cid-Aguayo, Beatriz E.; Sandoval-Nazal, Daniel; Carrasco, Juan Antonio (2013)
The Polanyian discussion about the embeddedness of the economy in social relations, finds a new stream through the social network analysis, from which is possible to map the cooperation relations that underlie economic ones. From the latter, this article shows the analysis of nine family-based economic entrepreneurships linked to a cooperative of services and agrofood products. Through personal networks analysis we mapped and highlighted the diversity of collaborations, monetary and non-monetary exchanges the entrepreneurships perform with their networks. In consequence, we characterized the support networks identifying the different economic exercises that take part in relation to the entrepreneurships. By this way, we accounted some relevant aspects such as the formality or informality condition, the entrepreneurships level, the networks' cohesion and the types of exchange, among other issues.
Keywords: embeddedness; rural entrepreneurships; social networks

How Moving to Quebec Has Affected My Theology - Baum, Gregory (Toronto Journal of Theology, 2010)
In this lecture given at the 2009 meeting of the American Academy of Religion in Montreal, Gregory Baum reports how moving to Quebec has affected his practical theology. He mentions three issues of great importance to this French-speaking society that demanded new ethical reflection on his part: the character of an ethically acceptable nationalism, the appropriate response to the cultural weight of English in North America, and an acceptable alternative to Canadian multiculturalism. Thanks to the Montreal-based Karl Polanyi Institute, Baum discovered Karl Polanyi's socio-economic thought critical of the unregulated market system, that differs from Marxism, attends to cultural and ethical issues, and reveals a certain affinity with Catholic social teaching. Polanyi offers a theoretical foundation for the social economy and community efforts to reform society from the bottom up.
Keywords: American Academy of Religion - Congresses; BAUM, Gregory; Montreal; Polanyi institute; Quebec; bilingualism; conferences & conventions; congresses; inter-culturalism; nationalism; religious life; religious studies

Social Economy and the fight against Social Exclusion: Preliminary remarks with reference to the Greek welfare state - Adam, Sofia (1st International Conference in Political Economy, 2010)
Recent academic discourse and European social policies highlight the (potential) effectiveness of social economy practices as a means to address social exclusion especially for the more disadvantaged social groups. Apart from terminological debates on the aforementioned troubled concepts, fundamental questions needs to be examined: To what extent social economy practices flourish as a result of policy shifts towards further commercialization of public social services or to what extent do they emerge from bottom up collective survival strategies? This paper attempts to address this question with reference to the political economy of the Greek welfare state.
Keywords: Greece; economic sociology; embeddness; political economy; social economy; substantive approach; welfare state

IPE and European Integration: Applying Karl Polanyi's 'the Great Transformation' - Copeland, Paul (2008)
European integration is usually studied within the realms of comparative politics. The multitude of empirical studies concerning the topic have been well suited to its numerous methodologies and analytical frameworks. Comparative politics however, usually ignores the question of why European integration has both progressively deepened and widened during the last thirty years. Therefore there is a distinct absence of how developments in the global political economy determine European integration. Such an approach fails to address the issues of power and constraint within the global economy. We would therefore expect the process to be examined within international political economy, yet there has been a relative neglect of European integration within IPE as it considers the process to be a mere regional response to global developments. This paper argues that European integration is a more complex process than IPE has considered and addresses its relative neglect by applying Polanyiâs 'the Great Transformation'. Firstly, this paper argues that existing comparative politics and IPE approaches to European integration have a number of shortcomings which limits their application. Secondly, to address these limitations this paper applies 'the Great Transformation' to European integration and argues there to be strong parallels between Polanyiâs theory and the process. Thirdly, the paper argues that European integration is much more than a simplistic regional response to globalisation. European integration has been a contradictory process oscillating between neoliberalism and the European Social model. This highlights not just the contradictions of European integration, but also what Polanyi termed the âmarket societyâ. ..PAT.-Unpublished Manuscript
Keywords: European integration; comparative government; globalization; international economic relations; international political economy; neoliberalism

Is Market Liberalization Pathological? Debating the Causes of Corruption in Chinese Banking - Eaton, Sarah (2008)
Neoclassical economists posit that the freeing of market forces will lead, ceteris paribus, to a reduction in levels of corruption. There are several mechanisms through which this hypothesized effect is channeled, the most important of which is competition pressure brought by the entry of foreign firms into the domestic market. The empirical leverage of this approach has been strongly challenged by events of recent years. In China and Russia, market liberalization has not had the expected effects: corruption has exploded alongside market opening. Why? The view among many economists is that the benefits of market opening were stymied by the political logic governing the process of reforms (e.g. cronyism in privatization, trade policy protection of inefficient domestic firms et cetera). The Polanyi-inspired counter-claim is that reform-era corruption is itself an effect of the disembedding of the political economy. My research on corruption in the Chinese banking industry lends empirical insight to the debate. Because the Chinese market is variegated, with some firms being much more exposed to competition than others, there is the opportunity to test these explanatory variables against corruption levels in different segments of the market. On the basis of original fieldwork conducted in China, this paper suggests that the neoclassical economists faith in market opening as an anticorruption mechanism is unwarranted. ..PAT.-Unpublished Manuscript
Keywords: China; banking industry; corruption; disembeddedness; ethics; market liberalization; white collar crimes

Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization - Busmann, Nadine (2007)
Reconfiguring the Terrain of Cultural Governance in Mexico: The Role of the Mexican Film Community in the Era of Neoliberal Globalization Embracing the dominant neoliberal project, many Mexican elites have prioritized economic growth and market logics over broader social goals. The unleashing of market forces globally,and the adoption of neoliberal policies nationally have had a significant impact on local communities and national culture in Mexico. Focusing on Mexican cultural production, this paper explores the shifting terrain of political struggle in the Mexican film industry. One of the central concerns of this paper is what processes and on what authority the imagined political community in Mexico is constructed, reconstructed, and reproduced in the current era of neoliberal globalization. Historically, political contestation among political, cultural and business elites has been central to the perpetuation of the national cultural project, in this paper, it is argued that the changing political landscape in Mexico has created new conditions for contestation providing sites for previously marginalized forces to challenge the hegemony of neoliberalism.Conceptualising neoliberal globalization and its application by Mexican elites in Polanyian terms?as a double movement?the paper examines the consolidation of the Mexican film coalition as a counter-movement, driven by cultural elites, which emerged to contest the hegemony of market driven politics. In this regard the paper analyzes the ideological and material foundations of this movement. Further, it examines the coalition´s efforts to create a social base from which to reshape the state´s politico-cultural agenda to ensure the survival of an indigenous film industry, thus providing (sub)national identities with an image and voice in the face of globalizing forces. It suggests that organic intellectuals built collective political agency upon the conviction that neoliberal globalization is to be resisted insofar as it subjects the nation to transnational?and hence alien?cultural, political and economic forces. Lastly, it challenges the assumption that in challenging the hegemony of neoliberalism the film community is anti-capitalist. As the evidence will reveal the motivating factors and ideological foundations driving the efforts of the film community are much more complex. ..PAT.-Unpublished Manuscript
Keywords: Mexico; cultural production; elite (social sciences); globalization; international studies; neoliberalism; social goals

Searching for the Theory of Practice behind the WTO's Commodification Mandate - Göpel, Maja (2007)
When trying to understand the origins of the collapse of nineteenth-century civilization, Karl Polanyi identified a Great Transformation into a "starkly utopian" Self-Regulating Market (SRM). This shift entailed 2 elements: a wide-ranging re-regulation of organization and control of production processes, and the development of economic liberalism as a body of thought that provided justification of a new set of public policies that facilitated a transformation of land (nature), labor (people), and capital (money) into "fictitious commodities." Even though these factors have not originally been produced for sale, they are now organized by purchase-logics and their value determined by market signals. Philosophy of praxis approaches point out that this process of transformation is never complete. Neither the ?discovery? of new commodities, nor the expansion of market logics are natural, but the outcome of socio-political struggles. New agreements of the World Trade Organization for example render ever more elements of social life and nature as ?trade related? and under its auspices the next great commodification wave unfolds. This paper traces which type of knowledge publicly justifies the resulting floods these policies release before comparing it with concrete negotiated outcomes and their impacts. The final discussion will circle the question to which extent ?objective? science influences policy-making - or if subjective selection of sciences supports policy-selling. ..PAT.-Unpublished Manuscript
Keywords: World Trade Organization (WTO); commodification; ideal types; institutionalism; international trade; manufacturing processes; methodology; policy sciences; trade regulation

The Intellectual Commons vs Intellectual Property: Marxian and Polanyian Perspectives on Intellectual Capital, including Remarks on Primitive Accumulation - Jessop, Bob (2007)
This paper explores the increasing significance of intellectual property rights for the appropriation of surplus value in capitalism. Building on Marx's analysis of the value form and extending it to the commodification of knowledge, it develops a Marxian critique of informational capitalism based on the basic categories of value theory; inter alia, this looks at the commodification of knowledge from the viewpoint of commodity fetishism, the enclosure of traditional knowledge, the formal subsumption of intellectual labour, the real subsumption of intellectual labour, and the role of intellectual property rights as a contradictory means to support the average rate of profit for firms specializing in immaterial production (whilst enabling them to appropriate monopoly profits). The second part of the paper inquires whether these arguments lend support to a Polanyian interpretation of knowledge as a fictitious commodity. On the basis of the arguments already deployed, plus further arguments, it is suggested that knowledge can function as a non-commodity, a quasi-commodity, a fictitious commodity, a real commodity, and as fictive capital. This has interesting implications for the concepts of primitive accumulation and accumulation through dispossession. ..PAT.-Unpublished Manuscript
Keywords: Marxist philosophy; capitalism; commodification; intellectual property; political doctrines

Four Horsemen of the Apocalypse: Marx, Weber, Schumpeter, and Polanyi - Özel, Hüseyin (ICAPE Conference: “Economic Pluralism for the 21st Century”., 2007)
This paper is an attempt at developing an analytical framework that could be helpful to understand the unstable character of the capitalist society, by drawing upon the work of four important thinkers: Marx, Weber, Schumpeter, and Polanyi. It is argued that all four share a similar vision towards capitalism, and that they are all indispensable for the thesis that the working of capitalism undermines its own institutional structure, and thus make the reproduction of the capitalist society a contradictory process. The paper advances three theses in regard of these thinkers: first, being various representatives of the German “expressivist ” tradition, they conceive human history as displaying two antinomical tendencies at the same time; namely, human self expression through creative action vs. the loss of freedom due to increasing rationalization, alienation, and domination; second, capitalism should be seen as a decisive step towards more rationalization and therefore the loss of freedom, even if it creates the preconditions of the self-realization of the “species-being”; and third, they all believe that the very success of capitalism is the basic cause of its failure.
Keywords: MARX, Karl, 1818-1883; SCHUMPETER, Joseph Alois, 1883-1950; WEBER, Max, 1864-1920; alienation; creative destruction; double movement; iron cage

What's Left in the City? What's Right in the Hinterland?: Urban Political Economy in Contemporary Latin America - Goldfrank, Benjamin; Schrank, Andrew (2006)
This paper accounts for the initial divergence and subsequent convergence of two types of urban political economy-neoliberal and socialist-in late twentieth and early twenty first century Latin America. Part 1 identifies the ideological differences between the two types of city as well as their implications for public policy. While neoliberal cities prioritize accumulation, and therefore use tax breaks, regulatory rollbacks, and the repression of organized labor to attract and retain foreign direct investment, their socialist rivals prioritize distribution, and therefore use social funds,microcredit arrangements, and participatory institutions to employ and empower their citizens. Part 2 treats the emergence of municipal neoliberalism as a secondary city or hinterland reaction to the growth of urban primacy or bias in the 1960s and 1970s. While industrial interests in population centers like Mexico City and São Paulo reaped the rewards of import-substituting industrialization, and therefore organized to defend their gains, their agro-commercial rivals paid a high price for tariffs and foreign exchange controls, and therefore deployed free trade zones (and similar incentives) in places like Chihuahua and Salvador to offset or compensate for the growth of urban primacy. Part 3 traces the origins of municipal socialism to the breakdown of ISI and the accompanying debt crisis in the late twentieth century. While neoliberal municipalities had already embraced the world market, and therefore welcomed structural adjustment at the national level, their socialist rivals feared globalization, and responded with a variety of compensatory measures of their own designed to increase the "social wage" not only in Mexico City and São Paulo but in other major cities like Caracas, Montevideo, and Lima. And, finally, Part 4 concludes by offering a Polanyian interpretation of the seemingly odd convergence of neoliberal and socialist municipalities today-suggesting that, whatever their ideological preferences, municipal authorities must balance accumulation with distribution if they are to survive and prosper in a globalized world. ..PAT.-Unpublished Manuscript
Keywords: EPZ; Latin America; Latin America - politics & government; cities & towns; foreign investments; local politics; neoliberalism; participatory budgeting; political planning; socialism

The Dark Side of Embeddeness: The Construction of Economic space and Prestige in Italy 1896-1907 - Polillo, Simone (Conference Papers -- American Sociological Association, 2006)
The creation of a national economic space is the necessary structural condition for the unfolding of the "self-protective" measures of society that Polanyi analyzed for the post-WWI period, and that he saw as more generally arising in response to free market policies. A national economic space is itself the product of specific institutional arrangements, in particular the state agencies that allow the state to centralize the monetary system in its own hands: in the modern period, these have been central banks. By analyzing a longitudinal sample of the minutes of the meetings of the governing body of the Bank of Italy in its crucial transitional period at the turn of the century (1896-1907), this paper attempts to trace the historical process by which the Italian economy came to be understood as a national space. It shows that the creation of an area of economic prestige measured by the technical success of the central bank and the strength of its relationship with the Treasury was a crucial achievement of the liberal state. ..PAT.-Unpublished Manuscript
Keywords: Italy; World War I; banking industry; central bank; embeddedness; manuscripts; monetary policy; money; saving and investment; self-protective measures; state

Retelling the Great Transformation - Steinberg, Marc (Conference Papers -- American Sociological Association, 2006)
In this paper I partly retell Polanyi's narrative of the industrial revolution found in his Great Transformation. I discuss how new labor laws consolidated in the 19th century created a legal structure of coerced contractual labor, that did not fit the ideals of free market economics. My retelling focuses on how capitalists in some industries relied on legal coercion of their workers as a means of discipline and labor process control. Through this retelling I demonstrate that Polanyi was still beholden to neo-classical economics in his historical account, errantly seeing the rise of a free market in labor with the Poor Law reforms of 1834 when in fact no such freedom existed. Therefore, he could not provide a fully-fledged institutional analysis of economic embeddedness that lies at the core of his theory. To realize a fully-developed institutional analysis I argue that we need to bring class conflict back into the narrative of institutional change through an analysis of legality and its transformation. I partly map out the outlines of a revised institutional analysis that places emphasis on the spatial organization of power, with 'stateness' conceptualized as a variable in which political power (and more especially authority) is scrutinized as historically accreted institutional structures. I also emphasize the historically specific role of the 'local state' in this narrative. ..PAT.-Unpublished Manuscript
Keywords: capitalists & financiers; criminal procedure; industrial laws & legislation; industrial relations; institutional embeddedness; labor laws & legislation; labour laws & legislation; law; quality control

Embeddedness as a Process - Chajewski, Leszek (Conference Papers -- American Sociological Association, 2005)
This article describes a strategy of modeling embeddedness of economic behavior as a process, as opposed to viewing it as a time-independent relationship between behavior and a social factor in which it is subsumed. I first reconstruct Polanyi's classic processual model of embeddedness and derive from it a set of intuitive tests, which are then applied to key modern approaches in economic sociology: structural, neo-institutional, neo-weberian and Fligstein's embeddedness-as-identity-formation approach. Finally, I describe main analytic and empirical consequences of the processual approach to embeddedness. Key among these consequences is that not all forms of embeddedness are of equal significance, therefore, economic sociology's empirical focus should shift from demonstrating that behavior is more likely to be embedded than not, to the forms of economic behavior that are likely to dominate alternative types of behavior.
Keywords: cultural and neo-weberian perspectives in economic sociology; economic sectors; economic systems; embeddedness; embeddedness and identity formation; embeddedness process; empirical research; forms of economic integration; market transitions; neo-institutionalism; new economic sociology; social factors; social status; socioeconomics

"Economic Life, Institutions, and Social Action: Reflections on Polanyi's Approach to Studying Economic Life" - Gemici, Kurtulus (Conference Papers -- American Sociological Association, 2005)
The article focuses on the relevance of economist Karl Polyani's economic theories and tries to analyze if his book titled "The Great Transformation," could be considered as the foundation of current economic sociology and international political economy. The author of the article says that Polayni's theories focuses on contemporary economic sociology, market economy's self-destructive approach and consideration of the market economy as integral part of the society. His work on institutedness and economy's embedness in society are working as base for most of the challenging theories in economic sociology.
Keywords: Great Transformation, The (Book); capitalism; economic behavior; economics; embeddedness; institutions; methodology; socioeconomics

What Can Marxists Learn From Polanyi? - Özel, Hüseyin; Yılmaz, Erdal (10th International Polanyi Conference: “Protecting Society and Nature from Commodity Fiction”, October 13-16, 2005, 2005)
The starting point of this paper is this comment by Rhoda Halperin on the relationship between Marx and Polanyi. Our objective is, however, to examine how reading of Polanyi could be useful to understand, or supplement, Marx’s own views on both capitalism and the “human condition” in general, rather than vice versa. In this regard, we argue first that those followers of Polanyi who believe that Marx should be treated as a rival of Polanyi, and that Marx’s “historical materialism” and his critique of capitalism is economically (or technologically) determinist, mechanistic, and reductionist, either misunderstand or misrepresent Marx.. We believe that these properties should be taken as representing the position that could be called as “vulgar” Marxism, rather than representing Marx’s own position. This type of “vulgar” Marxism is first of all positivistic or scientistic in its outlook; that is, it maintains the positivistic distinction between facts and values and thus considers ethics as being trivial in understanding and resisting capitalism. Secondly, its “materialistic conception of history” is guilty of the “economistic fallacy”, since it overlooks the fact only under capitalism do we have an “economic society”. Third, its class conception is mechanistic and reductionistic in that every act of resistance to capitalism must be explained in terms of, and carried out through, class struggle. Last, but not least, the “vulgar” Marxism is fatalistic in the sense that it maintains the view that capitalism will inevitably be collapsed through class struggle. We believe that none of these charges can be sustained if one considers Marx’s work in its entirety, and that there are important affinities and overlaps between Marx and Polanyi.
Keywords: MARX, Karl, 1818-1883; critique of capitalism; fictitious commodities; substantiveness

Antecedents of Resistance: Populism and the Possibilities for Democratic Globalization - Plante, David J.; Niemi, William L. (Conference Papers -- American Political Science Association, 2004)
Globalization is often portrayed as a new and unique phenomenon to our times. However, the dependence of American society upon global markets is not new. American Populists of the 19th century faced a similar matrix of political economic constraints. The Populists faced such challenges as the expansion of international trade, a deflationary international monetary order, integrating global capital markets, dependence on credit, and a political system unable to effectively regulate economic activity to public ends. In short, they responded to a system that from their perspective emphasized corporate profits at the expense of democracy. The Populists goal was to create a more democratic political economy in the face of these constraints. Today globalism has been countered by a diverse series of previously unconnected social movements. This paper argues that these movements are part of a rich tradition of democratic responses to the dislocations resulting from attempts to internationalize and commodify all social relations. As such, these 19th century movements offer instruction in the confrontation between democracy and capitalism in its latest iteration. For example, one important continuity between resistance to globalism today, is the use of democratized traditions of moral economy arguments to confront developing inequalities. Successful fair trade alternatives to free trade similarly depend upon moral economy arguments. Despite the inequalities resulting from globalization, challenges from the democratic promise have endured.
Keywords: capital market; capitalism; corporate profits; democracy; fair; globalism; globalization; international trade; monetary policy; populism; trade

Economic Sociology’s Legacy to Corporate Governance, 2004 - Kahn, Faith Stevelman (Conference Papers -- Law & Society, 2004)
This paper explores the intellectual tradition of Max Weber,Emil Durkheim, Joseph Shumpeter and Karl Polanyi — economic sociologists whose work has been largely ignored by corporate governance scholars focused on the more traditional areas of economics. The foundation laid by Weber is the central focus of the paper. Weber's writing in Economy and Society laid the groundwork for an approach to the study of firms and markets that diverges significantly from that in of the neoclassical economic model. Weber viewed firms and markets as being deeply embedded in and inseparable from the larger systems of social values and social structures that make a society durable. He grounded his view of economic action in a view of social action. Social actions are all deliberate (meaning purposive, which would include deliberately passive) acts undertaken in contemplation of others' acts and reactions. Transactions in money are generally social actions, since the value of money is determined by what people will decide to give you for it! Economic actions are constantly ormed by patterns of meaning, systems of power and social systems (the family....) that underlie them. From this perspective, the growth of the firm has as much to do with the need for rationalization and the rational/economic division of labor (esp. in a condition of limited liability) as it does with any immediate reduction of transaction costs. Rationality ( the struggle for meaning and systems that order chaos) is as pressing a force as efficiency. Recent writing in economics has come close to building a bridge back to economic sociology, especially with its interest in the effects (or lack of) trust in economic transacting as well as other "behavioral" variations. Economic sociology pursues these departures from qualitative rationality at the level of social structure, rather than individual psychological aberrancy. This paper tries to broader this more "socially" oriented view of the behavior of human beings in firms and markets. This intellectual background is related to contemporary issues in corporate governance legislation, and especially the Sarbanes Oxley reforms and then the increased demand for independent directors at public companies and mutual funds.
Keywords: DURKHEIM, Emile; WEBER, Max, 1864-1920; corporate governance; economic sociology; social action; social structure; socioeconomics

Disembedded Liberalism: Why global - Borowiak, Craig (Conference Papers -- Midwestern Political Science Association, 2004)
Bringing together democratic theory and international political economy literatures, I begin with the thesis that economic globalization is undermining the embedded liberalism of the post WWII era. Embodied in the Keynsian welfare state, embedded liberalism held out democratic avenues for disaffected groups to hold political actors responsible for suffering induced by market forces. Transformations in the global economy, however, constrain the options available to governments and curtail avenues of democratic accountability. Some have argued that the market itself can provide an adequate alternative. This view is deeply flawed. Drawing from the economic theory of Hayek and Friedman, I discuss how markets can operate as accountability mechanisms. I then turn to Karl Polanyi to discuss how markets that become disembedded from social contexts induce severe consequences for society and the environment. These consequences exceed what markets alone can account for. What’s more, as Habermas has observed, the system logic of markets is incompatible with the deliberative contexts in which democratic decision-making takes place. To propose markets as the solution to democratic deficits is to miss the point that it is the substitution of markets for social regulation that generates many of the problems in the first place. It is also to ignore the ways markets undermine the very spaces in which legitimate solutions can be determined. Somehow the effects of market accountability need to be accounted for. For this, there can be no substitute for forms of democratic deliberation that are themselves not reducible to market pressures.
Keywords: economics; globalization; international relations; liberalism; markets

How likely is a Post-Smithist 21st Century? - Cole, Constance H. (Conference Papers -- International Studies Association, 2004)
The current understanding of U.S. hegemony rests on the assumptions of neoclassical theories of both the state and the market. While the service-dominated economy is considered post- Fordist, the rhetoric of the state focuses on institutions of democracy. To what extent is our understanding of democracy dependent on the prior assumptions that the economy is ‘free’? If we reexamine the assumptions about the links between state and economy, drawing on the work of Gramsci, and Polanyi the necessary link between state and economy assumed in our current neoclassical theory looks quite different. The thesis of this research is that hegemonic ideologies of the relationship of state and market reinforce the interests of the commercial class at the expense of any meaningful representation of the working classes. Reconceptualizing the links between state and market in terms of an economics subordinate to social relations beyond those of commercial interests indicates the possibilities of a ‘post- Smithist’ understanding of both the imperfections of neoclassical market theories, and of the narrowness of institutional analyses.
Keywords: Fordism; Smithism; United States; democracy; economics; economy; hegemony; international; political; post; theory

The Culture War Goes Global: 'Family Values' and the Shape of U.S. Foreign Policy - Kline, Scott (Conference Papers -- International Studies Association, 2004)
Examines a neoconservative-religious right nexus that has emerged in and around the Bush White House. Discussion on the work of Karl Polanyi to examine a paradoxical tension that exists between U.S. nationalism and the promotion of a free-market economy; Family values nationalism and free market capitalism; Proposed two areas of critique that have been influenced by the work of Christian realists.
Keywords: United States; capitalism; economic policy; free enterprise; international studies; nationalism; neo-conservatism; political doctrines

The Reconfiguration of the State under Economic Conditionality and the Creation of Hollow Democracies ? With Illustrations from Zambia - Lloyd, Peter (Conference Papers -- International Studies Association, 2004)
This paper will explore the linkages and contradictions between the promotion of democracy and the application of economic and political conditionality in Southern Africa, with particular reference to Zambia. Many electoral democracies have emerged in Africa in the last decade in conjunction with and partially as a consequence of the conditions applied to loans by bilateral and multilateral donors. It will be argued that the process of conditionality and the neoliberal policies applied actually inhibit the emergence of substantive democracy and present a threat to the consolidation and longevity of even minimal forms of liberal democracy. The conditions applied to aid represent an attempt to reconfigure the activities, capacity and capabilities of the state. Most significantly, they involve the imposition of a neoliberal economic model which is seen as technically necessary to tackle economic crisis and which due to the leverage offered donors by the indebtedness of recipient countries is uncontestable, yet require active state intervention to achieve (Polanyi’s insight that the creation of self regulating markets require regulatory state activity). A major area of state policy is thus placed beyond accountability to the electorate of the recipient country; this is also true of many aspects of political and social policy. The process of negotiation between the International Financial Institutions and representatives of countries (most often the President and a small group of politicians and advisors from the finance ministry) also promotes a concentration of power within the state as representatives must be able to adopt positions on the behalf of their country and enact agreed policies from the top down. Conditionality thus involves a reduction in the democratic accountability of the state in three ways: Firstly, as political authority shifts upwards to the international sphere, to the IFIs and donor community; secondly as power is centralised within the presidency and finance ministry; thirdly, the scope of democracy is limited as liberalisation and the strict separation of politics and economics are enforced, placing many elements of economic life beyond the reach of democratic institutions. Applying this framework to Zambia, it will be argued that consequently a very limited and hollow form of democracy where most of the important political and economic processes affecting people’s lives are unaccountable to them has been created, and that increasing disillusionment and political volatility are ensuing, possibly representing a threat to even this minimal democracy.
Keywords: South Africa; democracy; economics; international studies; political doctrines; political science

The Great Transformation II: Human Rights Leapfrogging in the Era of Globalization - Howard-Hassmann, Rhoda (Conference Papers -- American Political Science Association, 2003)
Whether globalization will result in improvement or deterioration in protection of human rights is not a matter that can be observed in the short term. Globalization is, in effect, the second ‘great transformation’ (Polanyi) spreading capitalism over the entire world. In consequence, many of its short-term effects will be negative. Nevertheless, its medium and long-term effects may well be positive, as it impels social changes that will result in greater moves to democracy, economic redistribution, the rule of law, and promotion of civil and political rights. Capitalism is a necessary, though hardly sufficient condition for democracy: democracy is the best, though not the inevitable, political system to protect human rights. This does not mean that the non-Western world will follow the exact same path to protection of human rights that the Western world followed. The West had a singular advantage: it was not expected to protect human rights during its own era of economic expansion. Thus, the West was able to practice slavery, expel surplus populations, and colonize other parts of the world. Genocide and ethnic cleaning were permissible state activities. The non-Western world does not enjoy the advantage of human rights lawlessness. It does, however, enjoy other advantages occasioned by the presence of human rights. There is a global communications network and a global pro-human rights social movement. There is also the movement to global governance. Finally, and paradoxically, there is the global social movement against globalization, which forces some reflection upon its deleterious consequences. Thus, the non-Western world benefits from geographical and chronological human rights ‘leapfrogging’. This, along with the social changes that global capitalism and industrialism may impel, may mean that the medium and long-term consequences of globalization are positive for human rights.
Keywords: capitalism; democracy; globalization; human rights; human rights advocacy; social change

The World-Historical Origins of Pan-Islamic Nationalism in Iran - Araghi, Farshad (Conference Papers -- American Sociological Association, 2003)
In examining the world-historical context of the rise of pan-Islamic nationalism in Iran, this paper posits Islamic fundamentalism as a modern and global (rather than premodern and local) movement. Drawing on Polanyi and linking economy, polity, and culture, this study traces the origins of pan-Islamic nationalism in Iran to the transformation of the world-market relations in the second half of the nineteenth century and the rise of the food/agrarian regime after 1870. It shows that the relations of the state and the mercantile classes with the world market led to conflicting developments, viz., the national "contraction" of the state on the one hand and the international "expansion" of commercial classes on the other hand. The latter, in the course of their struggles for state representation, merged with the rising pan-Islamic reaction against European expansion in the "Islamic world." Pan-Islamism, by its capacity for articulating the economic nationalism of the mercantile classes in ethical terms, mobilized the masses of people for the struggle for the nationalization of the state. Hence, as a historical form, modernity and nationalism in the late nineteenth century Iran took a nonsecular character. Later, the Cold War politics revivified the pan-Islamic component of Iranian nationalism, creating the context for the rise to power of fundamentalism in the 1980s. The paper warns against the reification of place and culture rooted in binary conceptualizations of the local and the global phenomena.
Keywords: Iran; Islam; Islamic fundamentalism; culture; fundamentalism; market; nationalism; pan-Islamism; protestant fundamentalism; religion; religious fundamentalism; world; world-market relations

Labor Organizing and Neoliberal Politics - Rudy, Preston (Conference Papers -- American Sociological Association, 2003)
Neo-liberal policies and practices which impugn state policies as artificial interferences in the smooth operation of markets are at work globally, nationally and locally. Based on research about the Justice for Janitors in California, this paper examines the experience of the campaigns in San Jose and Sacramento. The paper is organized around a tension between two issues about markets that are explained by Karl Polanyi: their social reality as complex political constructions and the ideological justification for disembedding markets, aka the "Liberal Creed". In both campaigns the Justice for Janitors exposed the embeddedness of employers. On the other hand, in the ideological construction of their campaigns, the Justice for Janitors have not clearly confronted the "liberal creed" that justifies neo-liberal market practices. The JfJ campaigns have been successful at creating accountability for employers and politicians by revealing the concrete social relations within which markets are embedded, though they have largely failed to articulate an oppositional ideology to the liberal creed. At a minimum confronting this creed would place the state as central to the construction of market practices. The successes at instituting accountability of employers to democratic communities and the centrality of the state in securing that accountability will be undermined unless JfJ exposes the flaws of the liberal creed and clearly explains the importance of the state in securing the justice they seek.
Keywords: United States; ideology; labor; labour; liberal creed; liberalism; markets; neoliberalism; political planning

Place, Capitalism, and Democratic Efficacy - Kogl, Alexandra (Conference Papers -- American Political Science Association, 2002)
Keywords: DELEUZE, Gilles; capitalism; democracy; democratic; economy; efficacy; empire; place; political; theory

The Great Transformation at Sea: Fictitious Commodities and the Crisis of Marine Fisheries - Ziegelmayer, Eric (Conference Papers -- American Political Science Association, 2002)
Challenging contemporary debates concerning the regulation of ocean fisheries, this paper deploys theoretical insights developed by Karl Polanyi. In The Great Transformation, Polanyi documented the consequences of the establishment of market economy upon European society, and thereby upon the entire planet. The concept of the self-regulating market, according to Polanyi was based on three "commodity fictions" of land, labor and money; the extension of this concept to all of the economic institutions of society he called "market utopianism." This paper extends Polanyi’s fictitious commodity thesis to the living resources of the ocean and argues that the roots of the contemporary problems of the world’s fisheries originate in the exposure of nature to a market economy. Concerned with the future governance of ocean resources and democracy in fishery regulation, the paper examines the globalization of the fishing industry in comparative and historical perspective to illuminate the validity of Polanyi’s theory. While there can be no final agreement as to the constitution of "good society", a useful starting point for debate is provided by the work of Karl Polanyi. A good society, he claims, is a society capable of producing goods, and a necessary condition of life in such a society is that human beings and nature are not treated as commodities
Keywords: capitalism; democracy; economy; fictitious commodities; fisheries; fishery policy; political; property; rights; saltwater fishing

The utopian character of the counter-movements : reading Karl Polanyi in the twenty-first century - Rondelez, Pieter (13th Global Studies Conference : Globalization and Social Movements : Familiar Patterns, New Constellations?, 2020)
In the introduction of the 2001 edition of The Great Transformation, Fred Block argues that we all have much to learn from the insights of Karl Polanyi. Relying on Polanyi’s arguments in the Great Transformation is not only useful in order to understand the history of market liberalism, but also for the contemporary debate on globalization and its contestation. The work of Karl Polanyi is inspiring a lot of academics nowadays who are studying the global uprisings since 2008. Some academics – like Block - argue that neoliberals embrace the same utopian visions of their predecessors which lead to counter-movements that are resisting marketization processes and its political and economic consequences. Relying on Polanyi’s work, I point to a danger of interpreting the current neoliberal order as a similar trend towards marketization as in the period that Polanyi is dealing with in his book. Misinterpreting the current marketization project raises questions not only about the feasibility of re-embedding the economy back into society, but also about the desirability of disembedding society from the economy. In concrete, I argue that the utopian character shifted from the marketization project to the counter-movements that are trying to resist and change it. This also raises questions about the role of social scientists in (studying) the process of social change in the twenty-first century.
Keywords: contemporary relevance; countermovement; globalization; marketization; utopia